1979
DOI: 10.1111/j.1755-3768.1979.tb00545.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Production of Steroid Cataract in Bovine Lens

Abstract: Fresh calf lesnses incubated in nutritive media containing dexamethasone phosphate or ouabain in concentrations ranging from 1 X 10(-4) M to 1 X 10(-8) M developed cortical opacification and showed significant inhibition of Na(+)-K(+) ATP'ase activity. Over a 3-day incubation period the decrease in Na+-K+ ATP'ase activity correlated well with the observed decrease in light transmission. The degree of enzyme inhibition and decrease in light transmission varied directly with the concentration of dexamethasone ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[12] Steroids cause an inhibition of the cation pump in the lens capsule the resulting electrolyte/water imbalance is responsible for cataract formation. [13]…”
Section: Factors Implicated In Cataractogenesismentioning
confidence: 99%
“…[12] Steroids cause an inhibition of the cation pump in the lens capsule the resulting electrolyte/water imbalance is responsible for cataract formation. [13]…”
Section: Factors Implicated In Cataractogenesismentioning
confidence: 99%
“…Although the association between topical and systemic steroid use and increased occurrence of posterior subcapsular cataract (PSC) has been known since 1960 [ 1 ], the mechanism behind this type of lens opacification has yet not been elucidated. Over the years, several mechanisms such as osmotic failure [ 2 , 3 ], metabolic disturbances [ 3 ], protein adduct formation [ 3 - 6 ], conformational changes due to oxidative stress [ 3 , 6 - 8 ], and receptor mediated changes [ 3 , 6 , 8 - 11 ] have been proposed to account for PSC formation, but the results are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that glucocorticoids exert their actions both directly on lens function as previously mentioned, as well as indirectly via the glucocorticoid receptor (GR) [ 2 , 4 , 7 , 8 , 10 , 11 , 21 - 23 ]. In the lens, the presence of a functional GR was discussed for long.…”
Section: Introductionmentioning
confidence: 99%